2013
DOI: 10.1186/1750-1172-8-197
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of cultured skin fibroblast cells derived from patients with triglyceride deposit cardiomyovasculopathy

Abstract: BackgroundTriglyceride deposit cardiomyovasculopathy (TGCV) is a rare disease, characterized by the massive accumulation of triglyceride (TG) in multiple tissues, especially skeletal muscle, heart muscle and the coronary artery. TGCV is caused by mutation of adipose triglyceride lipase, which is an essential molecule for the hydrolysis of TG. TGCV is at high risk for skeletal myopathy and heart dysfunction, and therefore premature death. Development of therapeutic methods for TGCV is highly desirable. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…In TGCV, abnormal intracellular metabolism renders cells incapable of using long-chain fatty acids (LCFAs) (3,4) (Fig. 1), which play major roles in producing ATP in normal heart.…”
Section: T Riglyceride Deposit Cardiomyovasculopathy (Tgcv) Is Amentioning
confidence: 99%
“…In TGCV, abnormal intracellular metabolism renders cells incapable of using long-chain fatty acids (LCFAs) (3,4) (Fig. 1), which play major roles in producing ATP in normal heart.…”
Section: T Riglyceride Deposit Cardiomyovasculopathy (Tgcv) Is Amentioning
confidence: 99%
“…Hence, the development of specific treatment for TGCV is an urgent requirement. Our previous in vitro experiments on fibroblasts derived from patients with TGCV showed that LCFAs, the major energy source for the normal heart, accumulate as TG in cytoplasmic lipid droplets owing to ATGL deficiency 10,11 . To resolve the above-mentioned toxicity of LCFAs, we explored the development of nutritional therapeutic agents from medium-chain fatty acids MCFAs for the following reasons: 1 MCFAs have a long and safe history as they have been used clinically for 50 years in patients with metabolic and neurological disorders 12 14 ; 2…”
Section: Introductionmentioning
confidence: 99%
“…2, a lipid droplet maintenance protein, was a possible biomarker candidate in the context of lipid metabolism using fibroblasts from TGCV patients (17). Therefore, we can detect small lipid droplets as a PLIN 2 protein mass in cardiomyocytes ( Fig.…”
Section: Hara Et Al Reported That the Overexpression Of Perilipin (Pmentioning
confidence: 95%